Law Enforcement of Fisheries Crime in North Maluku Province through Transcendental Paradigm - Hanafi, Muhammad Amin; Absori, Absori; Dimyati, Khudzaifah; Syawal, Ajid Abdul; Budiono, Arief (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Objective: This article aims to discuss the enforcement of customary law in North Maluku, the deliberation value in the BMA Sultanate of Ternate, and the implementation of customary criminal sanctions by the Badan Musyawarah Adat.Methodology: The methodology used in this study was legal research conducted in a non-doctrinal qualitative approach. In this study, the law is not only conceptualized as all the principles and rules that regulate human life in society but also includes institutions and processes that actualize the validity of these rules in society.Findings: Law enforcement of fisheries crimes is based on the provisions of Indonesian Law No. 45 of 2009 concerning Fisheries. Criminal provisions are regulated by Articles 84 to 104. One of them is about sinking the ship used to commit fishing crimes. Sanctions given to the fish theft (illegal fishing) perpetrators in territorial waters that have been determined by the local customary head are 1) warning; (2) monetary charges according to the agreement of the local customary community; and (3) boat (pajeko in Ternate) or motorboat seized by the sultanate to be used by the community through profit sharing.Utility: Customary Institute of Ternate Sultanate in 2018 has decided on three cases in the Kao bay area concerning fish catching. Besides the traditional law enforcement that is implemented by the Sultanate, North Maluku recognizes Sasi Customs (Adat Sasi), which is regulation of tradition that limits people for catching fish or taking other sources in a certain type and particular period. Thus, the ecological balance is still maintained.Novelty/Originality: The concept of transcendental law enforcement is substantially in line with the values in the Segulaha tradition that has been applied for a long time in North Maluku. In Segulaha customary law, there is a traditional element in a person who has the same soul with transcendental values by positioning revelation as the source of the law.Â Keywords: Law Enforcement, Fisheries Crimes, Transcendental Approach